2018
DOI: 10.1177/0194599817745284
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Inflammatory Markers, Survival, and COX2 Expression in Oral Cancer and Implications for Prognosis

Abstract: Objective Peripheral blood-derived inflammation-based scores, such as the neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), and the combination of platelet count and NLR, have recently been proposed as prognostic markers in solid tumors. The purpose of this study was to investigate the validity of inflammatory markers as predictive prognostic factors for locally advanced oral squamous cell carcinoma (OSCC). In addition, we evaluated the potential correlation between systemic inflammation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…Elevated levels of inflammatory biomarkers (e.g., C-reactive protein [CRP], interleukin-6 [IL-6], interleukin-8 , interleukin-10 [IL-10], tumor necrosis factor-alpha [TNF-], and white blood cells [WBCs]) are associated with risk and prognosis of chronic conditions, including cardiovascular disease [1][2][3] and cancer. [4][5][6][7][8][9] Recent studies have also suggested that periodontal disease [10][11][12] and sleep behavior 13,14 may increase the risk of chronic disease onset and progression through inflammatory mechanisms, and may be linked to each other. [15][16][17] Current evidence linking periodontal disease 18,19 and sleep behavior [20][21][22] to systemic inflammation focused primarily on CRP with limited evidence for WBCs or their products as inflammatory biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of inflammatory biomarkers (e.g., C-reactive protein [CRP], interleukin-6 [IL-6], interleukin-8 , interleukin-10 [IL-10], tumor necrosis factor-alpha [TNF-], and white blood cells [WBCs]) are associated with risk and prognosis of chronic conditions, including cardiovascular disease [1][2][3] and cancer. [4][5][6][7][8][9] Recent studies have also suggested that periodontal disease [10][11][12] and sleep behavior 13,14 may increase the risk of chronic disease onset and progression through inflammatory mechanisms, and may be linked to each other. [15][16][17] Current evidence linking periodontal disease 18,19 and sleep behavior [20][21][22] to systemic inflammation focused primarily on CRP with limited evidence for WBCs or their products as inflammatory biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclooxygenase-2 (COX-2), the enzyme that catalyzes prostaglandin synthesis, has been extensively investigated as a target in cancer therapy and prevention ( Wang et al, 2005 ; Zha et al, 2001 ; Gupta et al, 2000 ; Yoshimura et al, 2000 ; Krishnan & Feldman, 2010 ; Sun et al, 2018 ). COX-2 is overexpressed in putative cancer precursor inflammatory lesions in tissues such as breast and prostate, in a variety of cancer cell lines, as well as in macrophages and other cells in the tumor microenvironment ( de Cremoux et al, 2018 ; Sano et al, 2018 ). Calcitriol regulates the expression of several genes in the prostaglandin pathway; in vitro and in vivo studies demonstrate that calcitriol + nonsteroidal anti-inflammatory agents which inhibit COX-2 potentiate the growth inhibitory effects of calcitriol ( Davila-Gonzalez et al, 2017 ; Basudhar et al, 2017 ).…”
Section: Anticancer Effects Of Vitamin D Compoundsmentioning
confidence: 99%
“…As an important indicator of inflammation, the transcription factor p65 (NF-κB) reduces the expression of the downstream protein prostaglandin G/H synthase 2 (COX-2) and nitric oxide synthase (iNOS) by activated luteolin (MOL022) [51]. Studies have shown that COX2 may be affected by systemic inflammation, and the prognostic impact of COX2 expression depends on tumor characteristics [52]. Also, iNOS is the main mediator of inflammation, and iNOS can enhance inflammation and plays an important role in apoptosis [53].…”
Section: Inflammation Effects Modulementioning
confidence: 99%